PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEMBAKARAN HUTAN DI KABUPATEN INDRAGIRI HILIR PROVINSI RIAU MENURUT UNDANG-UNDANG NOMOR 41 TAHUN 1999 TENTANG KEHUTANAN - Rizana, Rizana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
According to Article 50 of Law Number 41 of 1999 about Forestry, it is affirmed that everyone is prohibited from burning the forest, but in 2018 there were still forest fires in Indragiri Hilir Regency, Riau Province with an area of approximately 50 hectares located in Concong District. The problem is how to enforce the law against forest crime in Indragiri Hilir Regency, Riau Province according to Law Number 41 of 1999 about Forestry? The method used in this research is socio-legal research. The results of this research are that the implementation of Law Number 41 of 1999 about Forestry against forest fires in Indragiri Hilir Regency, Riau Province has not yet proceeded as expected. The obstacles are the lack of public understanding of the benefits of the forest for the long term and the lack of law enforcement in the case of forest fires. Law enforcement is that Article 78 of Law Number 41 of 1999 about Forestry affirms that anyone who intentionally burns forest can be threatened with imprisonment and fines. In addition, if a criminal act of forest burning is carried out by a legal entity or business entity and / or on behalf of a legal entity or business entity, then the criminal sanction is added to 1/3 of criminal sanctions in Article 78 of Law Number 41 of 1999 about Forestry.